Oxford picture dictionary - Adelson-Goldstein, Jayme; Full House Productions ([New York] : Oxford University Press, 2010)
Reading of the English words in the Oxford picture dictionary. Can accompany monolingual as well as multilingual versions of the 2nd edition of the print dictionary.
Includes 20 videos and 12 animated stories and 4,000 pieces of downloadable art and 241 worksheets.
System requirements for IBM or compatible: Pentium II, 450 MHz processor; Windows 98, 2000, XP, Vista; 256 MB RAM; 700-750 MB hard-drive space; 16x CD-ROM drive; 32-bit color monitor (800 x 600 minimum resolution); sound card; mouse; speakers; printer.; System requirements for Mac: 400 MHz processor; Mac OX X v.10.2.x, 10.3.x, 10.4.x, 10.5.4; 256 MB RAM; 700-750 MB hard-drive space; 16x CD-ROM drive; 32-bit color monitor (800 x 600 minimum resolution); mouse; speakers; printer.
Keywords: English language -- Dictionaries -- Software; Picture dictionaries, English; Picture dictionaries, English -- Software